Harga minyak, perak, dan indeks pasar Indonesia dalam isu geopolitik global - Tuisan, Kelvin Rafel; Jacobs, Jeilyn (Yayasan Widyantara Nawasena Raharja, 2024)
The circumstances of global geopolitical in 2022 are likely to affect economic conditions in the world, including capital market activities. This study aims to determine the impact of changes in world oil and silver prices on market index conditions in Indonesia from March 1 2022 to December 31, 2022. Throughout the observation period, the Indonesian market index had a small average return and was less risky so it had less than optimal performance. In contrast, silver tends to have optimum performance because it has relatively high average returns and risks. The findings of this study also imply that changes in oil and silver prices tend not to have a significant impact on market indices in Indonesia. Under other assumptions, this study finds opportunities for changes in world silver prices to trigger an increase in market returns in Indonesia.